2019
DOI: 10.1089/ten.tea.2018.0142
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Tissue-Engineered Synovium Model to Study Osteoarthritis Progression and Treatment

Abstract: The synovium envelops the diarthrodial joint and plays a key regulatory role in defining the composition of the synovial fluid through filtration and biosynthesis of critical boundary lubricants. Synovium changes often precede cartilage damage in osteoarthritis. We describe a novel in vitro tissue engineered model, validated against native synovium explants, to investigate the structure-function of synovium through quantitative solute transport measures. Synovium was evaluated in the presence of a proinflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 70 publications
(82 reference statements)
1
22
0
Order By: Relevance
“…Further, MMP-3 is mainly expressed by fibroblasts and endothelial cells [62], indicating that changes to the synovium are in fact contributing to observations in Study 2. Previous in vitro work has suggested that DEX modulates synovium behavior to IL-1 insult [78], however the role of MMPs on synovium function is unclear. Ultimately, additional studies will be required to elucidate the mechanism of DEX-induced matrix remodeling in vivo.…”
Section: Discussionmentioning
confidence: 97%
“…Further, MMP-3 is mainly expressed by fibroblasts and endothelial cells [62], indicating that changes to the synovium are in fact contributing to observations in Study 2. Previous in vitro work has suggested that DEX modulates synovium behavior to IL-1 insult [78], however the role of MMPs on synovium function is unclear. Ultimately, additional studies will be required to elucidate the mechanism of DEX-induced matrix remodeling in vivo.…”
Section: Discussionmentioning
confidence: 97%
“…To overcome these limitations, scientists extended their research to other joint tissues such as the synovial membrane, which is composed of a heterogeneous cell population of fibroblasts and macrophages [ 77 ]. As for the synovium, the first preclinical studies encompassed testing 2D cultures of synovial fibroblast and cell lines such as RAW 264.7, K4IM; however, their major limitations included the lack of analyses on the synovial macrophages and extracellular matrix [ 78 , 79 ]. Indeed, the use of 2D culture models is more suitable for synoviocytes than chondrocytes, as this latter does not retain a stable phenotype over culture passages and limit the number of experiments [ 6 , 80 ].…”
Section: Pros and Cons Of In Vitro Inflammatory Models: Their Potential In Regenerative Medicinementioning
confidence: 99%
“…Notably, Hung, C.T. and his coworkers gave evidence of the biological relevance of lavage and synovectomy for OA through cocultures of synovial fibroblasts with cartilage and latex particles with IL1α and TNFα [ 78 ]. The feasibility of in vitro modeling the complex cross-talk between cartilage and the synovial membrane is challenging as the synovium and especially macrophages play a pivotal role in mediating cartilage matrix breakdown [ 24 , 81 ].…”
Section: Pros and Cons Of In Vitro Inflammatory Models: Their Potential In Regenerative Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…Different protocols for studying ST or isolating synovial cells (such as biopsy, immunohistochemistry, flow cytometry, molecular biology, in vitro cells, ex vivo explants, and cell lines) are available. However, the protocols used in the different studies could have positively or negatively influenced the results obtained [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%